The interaction of periodically distributed parallel cracks in anisotropic materials subjected to concentrated loads. (August 2018) - Wang, Peizhi; Ge, Peiqi; Bi, Wenbo; Ge, Mengran; Li, Long
Highlights: SIFs for periodic parallel cracks in anisotropic materials subjected to concentrated loads are obtained. The problem is dissolved into symmetric and anti-symmetric loading conditions. SIFs under distributed loads are calculated using the method of Green's function. Abstract: Parallel median cracks can be generated on the subsurface layer of brittle materials in engineering. The interaction of periodically distributed parallel cracks in an infinite anisotropic material subjected to a concentrated load is examined. The interaction problem is reduced to the solution of a longitudinal crack in a plate strip with zero normal displacement of longitudinal edges. Solutions for the Mode I stress intensity factors (SIFs) at the tips of the crack under a single concentrated load are found by the superposition of the SIFs due to the two pairs of concentrated loads, symmetric and anti-symmetric loads. Besides, the solutions of the parallel cracks under three kinds of distributed loads with a power function form are obtained using Green's function. Results show that the SIFs increase gradually with the increase of the normalized distance between the parallel cracks, which is the cracks shielding effect.